Evaluation of the Role of Teachers in the Utilization of Learning Media in Tukang State Elementary School Using Formative-Summative Evaluation Model Based on School Management - Widyaningrum, Rakhel; Sanoto, Herry (Journal La Sociale, 2025)
The role of teachers in utilizing learning media in schools reflects the needs and abilities in terms of development, adaptation of technological developments, and creating learning motivation for students to achieve learning goals optimally. In this case, school management has a role that can support the utilization of learning media to be applied by teachers in schools. The purpose of this study was to evaluate the role of teachers in utilizing learning media in SD Negeri Tukang, using the Formative-Sumative Evaluation Model which is associated with the stages of school management. The process of school management is the planning stage, the organizing stage, the implementation stage, and the supervision stage which involves evaluation. The methodology of this study is descriptive qualitative.TData collection techniques using questionnaires, interviews, and observations. Data analysis techniques using data reduction, data presentation, and drawing conclusions. The results of this study indicate that the role of teachers in utilizing learning media at SD Negeri Tukang has been implemented. However, most teachers do not maximize the use of media provided by the school, and lack the ability to utilize digital-based learning media that follow the development of the times.